Taxes in the Perspective of Islamic Law - St Saleha Madjid; Ulil Amri; A. Muh. Aidil (Universitas Muhammadiyah Makassar, 2024)
Taxes are essential for the growth of a country because they are a source of funds to facilitate development. However, there is a polemic regarding taxes from the perspective of Islamic law. Some scholars allow taxes, while others prohibit them. Ulama who allow taxes are of the opinion that taxes are a means of achieving mashlahah in maqashid sharia, namely achieving the common good. They see taxes as a tool to fund public needs, which is in line with sharia principles in advancing the welfare of the people. On the other hand, scholars who do not allow taxes argue that the law regarding taxes is not explicitly mentioned in the Koran. They argue that the only economic obligation that is clearly regulated in the Koran is zakat. Zakat is considered the only form of financial contribution required for Muslims, and therefore, taxes do not have a strong legal basis in sharia. This debate reflects various scholarly interpretations of religious texts and their application in modern contexts. Even though there are differences of opinion, both groups of ulama agree that the main goal is the benefit of the people, whether through taxes or zakat. The role of taxes in supporting development and public welfare remains an important issue that requires in-depth consideration in order to achieve a balance between religious law and the practical needs of the state